Cancer diagnosis and immunotherapy in the age of CRISPR. Issue 4 (20th December 2018) - Cook, Peter J.; Ventura, Andrea
Abstract: The explosion in genome editing technologies that has occurred in the past decade has revolutionized cancer research and promises to improve cancer diagnosis and therapy. Ongoing efforts include engineering of chimeric antigen receptor‐T cells using clustered regularly interspaced short palindromic repeats (CRISPR) to generate a safer, more effective therapy with improved performance in immunologically "cold" tumors, as well as clever adaptations of CRISPR enzymes to allow fast, simple, and sensitive detection of specific nucleotide sequences. While still in their infancy, CRISPR‐based cancer therapeutics and diagnostics are developing at an impressive speed and it is likely they will soon impact clinical practice. Here, we summarize their history and the most recent developments.